Loop-mediated isothermal PCR (LAMP) for the diagnosis of falciparum malaria. - Paris, D; Imwong, M; Faiz, A; Hasan, M; Yunus, E; Silamut, K; Lee, S; Day, N; Dondorp, A (2007)
A recently described loop-mediated isothermal polymerase chain reaction (LAMP) for molecular detection of Plasmodium falciparum was compared with microscopy, PfHRP2-based rapid diagnostic test (RDT), and nested polymerase chain reaction (PCR) as the "gold standard" in 115 Bangladeshi in-patients with fever. DNA extraction for LAMP was conducted by conventional methods or simple heating of the sample; test results were either assessed visually or by gel electrophoresis. Conventional DNA extraction followed by gel electrophoresis had the highest agreement with the reference method (81.7%, kappa = 0.64), with a sensitivity (95% CI) of 76.1% (68.3-83.9%), comparable to RDT and microscopy, but a specificity of 89.6% (84.0-95.2%) compared with 100% for RDT and microscopy. DNA extraction by heat treatment deteriorated specificity to unacceptable levels. LAMP enables molecular diagnosis of falciparum malaria in settings with limited technical resources but will need further optimization. The results are in contrast with a higher accuracy reported in an earlier study comparing LAMP with a non-validated PCR method.